Nurses in the community: a manpower study. Issue 4 (December 1979) - Hughes, J; Stockton, P; Roberts, J A; Logan, R F
Abstract : High priority is at present being given to the expansion of health visiting and home nursing services as part of the change of emphasis from institutional to community care. The aim of this study was to provide nurse managers in two regional health authorities with basic information about community nurses with could be used for service planning and development. The results of the study emphasise the particular problems of staffing the community nursing service in inner London, where home nurse and health visitors are younger, more recently appointed, and relatively less experienced than staff in other parts of the regions. High turnover rates and chronic recruitment difficulties in inner London prevent nurse managers from maintaining both the level and the quality of the services they aim to provide. Until these problems are remedied there is little prospect of achieving any significant shift in the balance of care in inner London.